Language Policy and Multilingualism: Assessing NEP 2020’s Approach to Language Education - Kadam, Sangeeta Rajaram (AG Volumes, 2025)
A child’s whole development is greatly influenced by the language that is used as the medium of education. The choice of a particular language for this purpose is difficult in a nation like India, where the population is multilingual and heterogeneous. Speaking hundreds of languages, 22 of which are recognised by the Constitution, multilingualism is an essential part of the nation’s composite culture. From the study of various research’s, who study on Language Policy and Multilingualism in NEP 2020 it concluded that the multilingual learners benefit from improved problem-solving skills, creativity, and a deeper understanding of different cultures, making them more globally competent. NEP 2020’s emphasis on multilingual education not only preserves India’s rich linguistic heritage but also promotes inclusivity and cultural pluralism. By integrating local languages into education while nurturing proficiency in multiple languages, the policy fosters national unity while preparing students for global opportunities.